Reclamation of salinized soils due to excess of fertilizers: evaluation of leaching systems and equations - José Leôncio de Almeida Silva; Sergio Nascimento Duarte; Demetrius David da Silva; Neyton de Oliveira Miranda (Dyna, 2019)
In regions with intense irrigation, the use of fertirrigation increases crop productivity, but excessive fertilizer application increases the risk of soil salinization. Therefore, this work used leaching equations to evaluate systems of remediation of soils salinized by excess fertilizers. The phases of the study were: salinization of soils in lysimeters, remediation of these soils, and measurement of salt concentrations in soils for comparison with estimates of empirical equations. The treatments combined soil remediation systems (continuous and intermittent) with five initial levels of soil salinity (2.0, 4.0, 6.0, 8.0, and 10.0 dS m-1). The experimental design was randomized blocks with six replicates. The Volobuyev equation best represented the salinized soil remediation in relation to the results obtained experimentally. The equations tested showed better performance in the intermittent remediation system compared to the continuous system.